Impact of intertidal area characteristics on estuarine tidal hydrodynamics: A modelling study for the Scheldt Estuary. (5th November 2017) - Stark, J.; Smolders, S.; Meire, P.; Temmerman, S.
Abstract: Marsh restoration projects are nowadays being implemented as ecosystem-based strategies to reduce flood risks and to restore intertidal habitat along estuaries. Changes in estuarine tidal hydrodynamics are expected along with such intertidal area changes. A validated hydrodynamic model of the Scheldt Estuary is used to gain fundamental insights in the role of intertidal area characteristics on tidal hydrodynamics and tidal asymmetry in particular through several geomorphological scenarios in which intertidal area elevation and location along the estuary is varied. Model results indicate that the location of intertidal areas and their storage volume relative to the local tidal prism determine the intensity and reach along the estuary over which tidal hydrodynamics are affected. Our model results also suggest that intertidal storage areas that are located within the main estuarine channel system, and hence are part of the flow-carrying part of the estuary, may affect tidal hydrodynamics differently than intertidal areas that are side-basins of the main estuarine channel, and hence only contribute little to the flow-carrying cross-section of the estuary. If tidal flats contribute to the channel cross-section and exert frictional effects on the tidal propagation, the elevation of intertidal flats influences the magnitude and direction of tidal asymmetry along estuarine channels. Ebb-dominance is most strongly enhanced if tidal flats are around mean sea level or slightly above. Conversely, flood-dominance is enhanced if the tidal flats are situated low in the tidal frame. For intertidal storage areas at specific locations besides the main channel, flood-dominance in the estuary channel peaks in the vicinity of those areas and generally reduces upstream and downstream compared to a reference scenario. Finally, the model results indicate an along-estuary varying impact on the tidal prism as a result of adding intertidal storage at a specific location. In addition to known effects of tidal prism decrease upstream and tidal prism increase downstream of additional storage areas, our model results indicate a reduction in tidal prism far downstream of intertidal storage areas as a result of a decreasing tidal range. This study may assist estuarine managers in assessing the impact of marsh restoration and managed shoreline realignment projects, as well as with the morphological management of estuaries through dredging and disposal of sediment on intertidal areas.